United for success against non-Hodgkin’s lymphoma: role and responsibilities of the nuclear medicine department (Hematology Meeting Reports, 2009)
Yttrium-90 90Y) ibritumomab tiuxetan is an immunotherapeutic agent that has recently been approved for the treatment of relapsed or refractory low-grade, follicular, or CD20+ transformed non-Hodgkin’s lymphoma (NHL). 90Y-ibritumomab tiuxetan has delivered highly encouraging responses in clinical studies and represents a major advance in the management of patients with difficult forms of NHL. This agent is notable for its emission of b radiation only, which minimizes or eliminates the need for radiation safety precautions normally associated with radiopharmaceuticals and permits treatment to be carried out in an outpatient setting. Moreover, dosimetry is not required prior to therapy for approved usage in the European Union, and preparation of the radiolabeled monoclonal antibody is straightforward and easily learned. Traditionally, nuclear medicine physicians have been solely responsible for the management of patients undergoing radiotherapy, but logistic, patient selection, and haematological safety considerations call for a multidisciplinary team approach to optimize outcomes with 90Y-ibritumomab tiuxetan. The team should include the haemato-oncologist or haematologist, immunopathologist, clinical nurse specialist, nuclear medicine physician, radiopharmacist, radiation protection specialist, and other nurses, junior and administrative staff, as appropriate. The team approach draws on a wide range of specialist skills and early data from a major UK institution show that treatment benefits are maximised when treatment is administered on a collaborative basis. Thus, 90Y-ibritumomab tiuxetan represents a significant therapeutic advance, and provides new opportunities for optimizing therapeutic outcomes through the multidisciplinary approach to patient care.